Unraveling traffic jam complexity: insights from elementary cellular automata and statistical physics - Baibolatov, Y.; Nalibayev, Y.; Kozhagulov, Y. (Recent Contributions to Physics, 2024)
The Nagel-Schreckenberg (NaSch) model is a foundational cellular automaton framework for modeling highway traffic dynamics. Despite its simplicity, the model reproduces key features of real traffic, including the spontaneous emergence of stop-and-go waves and phantom jams. This study investigates the critical transition from free-flow to congested traffic as vehicle density increases. Through extensive simulations on large systems, we analyze steady-state observables such as mean velocity, traffic flow, velocity variance, and the number of jammed clusters. A sharp transition is observed in both microscopic and macroscopic indicators, with velocity fluctuations peaking near a critical density that signifies the onset of jamming. To interpret this behavior, we develop a mean-field theoretical framework that predicts the critical transition point based on vehicle interactions and stochastic braking. The theoretical prediction closely matches the numerical location of the peak in velocity variance. Additionally, we study the formation and coalescence of jams, identifying a secondary peak in jam count at higher densities, where small clusters merge into large-scale gridlock. These findings provide a quantitative understanding of the jamming transition in traffic flow and highlight the relevance of nonequilibrium phase transition theory in transportation systems. The NaSch model thus serves as a paradigmatic example of how simple local rules can give rise to emergent collective phenomena and critical behavior.